Lena Larrieu: capstone - Larrieu, Lena, artist (Colorado State University. Libraries, 2015)
The artist's statement: I am drawn to clay as a material. It has the ability to create portals and bridges into different dimensions. This quality of clay enables me to bring images and figures from the picture plane into our physical world. My work is comprised of layers of decoration that play with different scales and textures that push the forms to be intricate but not overbearing. The creation of a large wall piece or a sculpture that is almost life size creates a larger presence in the field of vision and has intricate detail that can draw the viewer closer. My ideas are inspired by buildings and windows from countries in Latin America and the Middle East. I am interested in integrating these architectural components with sources from the natural world such as corals, trees, animals, and rocks. For example, some of my work is based on architectural forms that are overcome with textures from nature and where the original source is less apparent. In other work these ideas have a more direct dialogue with one another, where the pieces are referencing how we place architecture in relation to the natural world. I use my work to explore the discovery of hidden secrets lost and aged architecture has to offer.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.